The botany of desire [videorecording (DVD)] - Pollan, Michael; McDormand, Frances; Pollan, Michael (Distributed by PBS Distribution, 2009)
Shows how human desires are an essential, intricate part of natural history. The program will explore the natural history of four plants -the apple, the tulip, marijuana, and the potato - and the corresponding human desires - sweetness, beauty, intoxication and control. This two-hour documentary begins in Michael Pollan's garden, and roams the world, from the fields of Iowa to the apple forests of Kazakhstan, from a medical marijuana hot house to the tulip markets of Amsterdam.